2009
DOI: 10.1029/2009jg000990
|View full text |Cite
|
Sign up to set email alerts
|

The use of PARAFAC modeling to trace terrestrial dissolved organic matter and fingerprint water masses in coastal Canadian Arctic surface waters

Abstract: The optical properties of chromophoric dissolved organic matter (CDOM) were investigated in the Canadian Archipelago and coastal Beaufort Sea surface waters using fluorescence spectroscopy coupled with parallel factor analysis (PARAFAC). Environmental dynamics of individual components were evaluated and compared to salinity, in situ fluorescence, absorption at 312 nm (a312), dissolved organic carbon, and lignin phenol concentrations. A positive linear relationship between four fluorescent components and lignin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
148
2
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(171 citation statements)
references
References 40 publications
20
148
2
1
Order By: Relevance
“…It may result from biological activity and/or microbial reworking of plankton-derived DOM (Yamashita et al, 2008) and was found to be both sourced from land and produced in the ocean (Murphy et al, 2008). The fluorescence peaks of component 2 (C2) at excitation/emission wavelengths of < 260 (400)/475 nm is similar to previously identified terrestrial humic-like material or "A" peak (Coble, 1996;Stedmon et al, 2003Stedmon et al, , 2005bGueguen et al, 2012;Walker et al, 2009). Fluorescence of components 3 (C3) and 4 (C4) are of proteinaceous origin, namely tyrosine and tryptophan.…”
Section: Fluorescence Components From Parafac Analysissupporting
confidence: 49%
“…It may result from biological activity and/or microbial reworking of plankton-derived DOM (Yamashita et al, 2008) and was found to be both sourced from land and produced in the ocean (Murphy et al, 2008). The fluorescence peaks of component 2 (C2) at excitation/emission wavelengths of < 260 (400)/475 nm is similar to previously identified terrestrial humic-like material or "A" peak (Coble, 1996;Stedmon et al, 2003Stedmon et al, , 2005bGueguen et al, 2012;Walker et al, 2009). Fluorescence of components 3 (C3) and 4 (C4) are of proteinaceous origin, namely tyrosine and tryptophan.…”
Section: Fluorescence Components From Parafac Analysissupporting
confidence: 49%
“…Temperature-enhanced P transformations and SRP fluxes from sediments have been widely observed in lab incubations (House and Denison, 2002;Suplee and Cotner, 2002;James and Barko, 2004;Schulz and Herzog, 2004) and field temperature manipulations (e.g., Zhang et al, 2012). The consistent temperature dependence of SRP fluxes across sites is related to the fact that organic P mineralization and MnO 2 /Fe 2 O 3 reduction (two processes contributing to SRP release from sediments) can be enhanced at higher temperatures with intensifying organic matter (OM) decomposition.…”
Section: Effects Of Temperature On Transformations and Fluxes Of Docmentioning
confidence: 99%
“…Sodium azide has been reported to have no effect (Ferrari et al, 1996;Astoreca et al, 2009) but also to cause up to 10 % increase in absorption (Tiltstone et al, 2002). Patel-Sorrentino et al (2002) found that sodium azide had no measurable effect on the EEMs of two humic-like fluorophores.…”
Section: Review Of Storage Methodsmentioning
confidence: 99%
“…Hunter and Liss (1981) found small SA losses from samples dark-stored at 6 • C for up to a week, but an increase of 20 % after 34 days. Freezing of filtered samples at −20 • C is also widely used for CDOM storage (Coble et al, 1998;Murphy et al, 2008;Conmy et al, 2009;Walker et al, 2009;Gao et al, 2010;Spencer et al, 2010;Yamashita et al, 2010b) but again sample provenance appears to be important; highly coloured samples comprising mostly allochthonous OM tend to show greater changes during freeze/thaw than more optically clear autochthonousdominated OM samples. Two studies of a range of freshwaters found that after freeze/thaw, fluorescence intensities and adsorption coefficients showed both increases and decreases (Spencer et al, 2007a;Hudson et al, 2009), although overall CDOM loss was observed and protein-, humic-, and fulvic-like fluorophore intensities all declined (Hudson et al, 2009).…”
Section: Review Of Storage Methodsmentioning
confidence: 99%
See 1 more Smart Citation